2005
DOI: 10.1093/jn/135.8.1911
|View full text |Cite
|
Sign up to set email alerts
|

Grape Polyphenols Exert a Cardioprotective Effect in Pre- and Postmenopausal Women by Lowering Plasma Lipids and Reducing Oxidative Stress

Abstract: To evaluate the effects of grape polyphenols on plasma lipids, inflammatory cytokines, and oxidative stress, 24 pre- and 20 postmenopausal women were randomly assigned to consume 36 g of a lyophilized grape powder (LGP) or a placebo for 4 wk. The LGP consisted of 92% carbohydrate and was rich in flavans, anthocyanins, quercetin, myricetin, kaempferol, and resveratrol. After a 3-wk washout period, subjects were assigned to the alternate treatment for an additional 4 wk. The placebo consisted of an equal ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
229
1
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(248 citation statements)
references
References 36 publications
13
229
1
5
Order By: Relevance
“…Red wine consumption in healthy subjects also reduced urinary levels of prostoglandin F2-a, a marker of systemic lipid peroxidation (42). A similar effect on urinary isoprostane concentrations were observed in pre-and postmenopausal women following treatment with lyophilized grape powder for 4 wk (43). At the present time, no study, to our knowledge, has shown a relation between polyphenol consumption and reduced atherosclerosis in humans.…”
Section: Epidemiologysupporting
confidence: 66%
“…Red wine consumption in healthy subjects also reduced urinary levels of prostoglandin F2-a, a marker of systemic lipid peroxidation (42). A similar effect on urinary isoprostane concentrations were observed in pre-and postmenopausal women following treatment with lyophilized grape powder for 4 wk (43). At the present time, no study, to our knowledge, has shown a relation between polyphenol consumption and reduced atherosclerosis in humans.…”
Section: Epidemiologysupporting
confidence: 66%
“…For instance, red wine or red wine polyphenol supplementation to rats increased apoA1 and reduced apoB (59,61) . Similarly, the same effects were produced by the intake of freeze-dried grapes or concentrated grape juice by menopausal women or by healthy and haemodialysed subjects respectively (24,65,68) .…”
Section: Apolipoproteinsmentioning
confidence: 76%
“…In the case of LDL-cholesterol, significant reductions have been observed in studies in both animals (13,27) and in human subjects (24,29,33,65,68,69) , although other studies have reported no effect either in animals (11,70) or in human subjects (21,24,47,66,67) .…”
Section: Total Cholesterol Ldl-cholesterol and Hdl-cholesterolmentioning
confidence: 99%
“…Plasma TG and apolipoprotein B (apoB) levels are reduced by GSPE in normolipidemic rats, 12 and by lyophilized grape powder in postmenopausal women. 13 The lipoprotein profile is also improved in both healthy subjects and hemodialysis patients by concentrated red grape juice.…”
Section: Introductionmentioning
confidence: 99%